The Dynamic American Dream. Issue 4 (21st April 2020) - Wolak, Jennifer; Peterson, David A. M.
Abstract: The American Dream is central to the national ethos, reflecting people's optimism that all who are willing to work hard can achieve a better life than their parents. Separate from the support for the idea of the American Dream itself is whether the public believes it is attainable. We consider the origins and dynamics of the public's belief in the achievability of the American Dream. Is the American Dream a symbolic vision, rooted in political socialization rather than contemporary politics? Or does optimism about the American Dream follow from the viability of the dream, rising with economic prosperity and falling with declining opportunity? We develop a new macrolevel measure of belief in the American Dream from 1973 to 2018. We show that it moves over time, responsive to changes in social mobility, income inequality, and economic perceptions. As inequality increases, belief in the attainability of the American Dream declines.